Textual thresholds and their applications in the contemporary Iraqi theatrical text. The play of divinities by Ali Abd al-Nabi as a model - Esmaeel Mohammed Hashim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Through his research, the researcher tries to shed light on the peripheral textual thresholds, starting from the name of the composer, the title, the cover image, sub-headings, the introduction, the export and the dedication, all the way together with the technical procedures of the name of the printing press, the date of printing and its location, which became a parallel text to the original text. They constitute an important axis in the reception process. And also they are considered to be effective procedural keys to entering into the text space , the interpretation, decoding and interrogation, and how the Iraqi playwright could apply and use them in his theatrical texts.